Information and educational environment university: a structural-functional model of the chemistry learning process (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
The article deals with the peculiarities of creating a structural and functional model of the process of teaching chemistry with the use of information technologies of higher education. The main directions of application of information and educational environment in the study of disciplines of the chemical cycle are highlighted. The conditions of efficiency of introduction of information technologies in the educational process are determined.A theoretical model of the methodology of additional chemical education is developed based on the integration of the content of training and active use of information and educational environment (IЕЕ) and ICT. For decades, modeling has been one of the most current methods of scientific research, widely used in pedagogical research. Modeling method allows to combine empirical and theoretical in pedagogical research allows to combine while studying the pedagogical object experiment, to build logical constructs and scientific abstractions.Modeling as a universal form of cognition is used in the study and transformation of phenomena in any field of activity, it is the most common method of study of objects of different nature, including objects of complex social system, so this method is widely used by students, undergraduates, graduate students, PhDs in scientific research. The application of modeling is very closely related to a deep knowledge of the nature of educational phenomena and processes, the deepening of the theoretical foundations of the study. Modeling method opens for the pedagogical science the possibility of mathematization of pedagogical processes and has great potential. Also, the main forms of independent work of students with the use of multimedia technologies were highlighted.One of the most expedient and effective methods of collecting and organizing factors is the information modeling method. The development of theory and practice of modeling the process of teaching chemistry at the university involved scientific research and problem solving in different subject areas, special methods of information submission for the construction of electronic tools involved in automation of information tasks.
Keywords: model; modeling; structural and functional model; information and educational environment; information, and communication technologies